Analisis Kesalahan Ejaan yang Disempurnakan (EYD) dalam Proposal Skripsi Mahasiswa - Ummul Khair (Institut Agama Islam Negeri Curup, 2018)
This text study objective was to determine how much the level of student writing errors made in the use of written language in developing a thesis proposal. The method used in the research data penganalisissan this text is the text method , which collects a number of text samples, further reading and doing analyzing student writing done , and also uses descriptive method of analysis. As the results, 1) error writing uppercase (capital) in the student proposal STAIN Curup VIII semester of academic year 2012/2013 as many as 850 words, with a percentage of 40.59 %; 2) error writing spelling on student proposals STAIN Curup VIII semester of academic year 2012/2013 as many as 681 words, with a percentage of 32, 52 %; 3) error writing prepositions (di, ke and dari) the student proposal STAIN Curup VIII semester of academic year 2012/2013 as many as 282 words, with a percentage of 13.46 %; 4) error writing punctuation dot (.), comma (,), colon (:), semicolon (;), and quotes (